Digital media and maternal healthcare among young women in Kenya: Use, patterns, and perspectives - Momanyi, Lydia Kwamboka; Mogambi, Hezron (C-DISC, 2023)
This study aimed to examine the relationship between digital media use and maternal health care utilization among young pregnant mothers in Kenya. Using a mixed methods approach combining questionnaires and focus group discussions (FGDs), data were collected from pregnant women and new mothers aged 19–35 years in Nairobi. Using Microsoft Excel Data Analysis ToolPak Ver. 2016, primary data were statistically analyzed, while FGD data were subjected to thematic analysis and narrative interpretation. Findings revealed that 88% of participants preferred internet searches for information, 92% used different digital media during pregnancy, 56% used pregnancy apps, and 9% abstained from digital media for maternal health information. The study concludes that, in addition to the continued importance of traditional sources of information, digital media have a significant impact on the use of maternal health services. It recommends that health care providers actively usedigital media, especially apps, as educational tools to disseminate reliable information to young pregnant women and new mothers in Kenya. It also recommends that planners and policymakers incorporate digital media into maternal health interventions to increase their effectiveness.